Diversity and Religious Moderation: The Relationship between Diversity Knowledge and Religious Moderation Awareness - Husni, Husni; Bisri, Hasan; Anwar, Yayan Khaerul (Jurnal Penelitian Pendidikan Islam, 2023)
The objective of this study is to enhance understanding of variety, knowledge, and awareness of religious moderation among potential Islamic religious education teachers. The present study employs a quantitative methodology and utilizes correlational analysis as the primary research tool. This study aims to investigate the potential correlation between diversity in one variable and diversity in other variables. The empirical findings of the study provide evidence supporting the premise that there exists a significant positive correlation between awareness of variety and religious moderation. The statistical analysis reveals that the F value is 47.523, indicating a significant relationship. The associated probability value (sig.) is 0.000, further supporting the significance of the findings. The multiple linear regression model is deemed significant and the research hypothesis is accepted due to the probability value (sig.) of 0.000, which is significantly smaller than the conventional threshold of 0.05.